Carbon Dot-Based Photodynamic Therapy for Clinical Treatment of Nonmelanoma Skin Cancer - Romero, María Paulina; Garzón-Romero, Cristina C.; Cruz, Fabian; Verdugo, Carla; Bastidas, Deysi M.; Mendez, Katty M.; Cabrera, Franklin (Dermatology Practical & Conceptual, 2026)
Introduction: Nonmelanoma skin cancer (NMSC), mainly including basal cell carcinoma (BCC) and squamous cell carcinoma (SCC), is the most often diagnosed malignancy worldwide, frequently necessitating substantial healthcare resources due to its elevated incidence and recurrence rates. Objective: This study evaluated a combined procedure of curettage and carbon dots-photodynamic therapy (CDs-PDT) to treat skin cancer superficial BCC (S-BCC), nodular BCC (N-BCC), invasive microglandular BCC (IMG-BCC), solid surface extension BCC (SS-BCC), and in situ SCC (Bowen). Methods: Twenty-two patients (15 male and 7 female) with 27 lesions were treated with this combined procedure. In all cases, curettage was performed first, followed by CDs-PDT. Previously, CDs had been used as cream or hydrogel vehicles for photodynamic treatment. PDT was administered in four or eight sessions, depending on each patient's response. The results indicate that PDT-based cream/CDs achieved complete responses in S-BCC, N-BCC, and SS-BCC and partial responses in the elimination of Bowen's lesions. PDT-based hydrogel-cream/CDs showed partial responses in S-BCC and SS-BCC. Results: This research found, for the first time, that PDT-based cream/CDs have better results than hydrogel-cream/CDs for the treatment of nonmelanoma skin cancers BCC and Bowen disease. Rapid healing was noted following each PDT session-based CD, and no pain was reported during irradiation. Conclusion: These results indicate that CD-based PDT could be used in the clinical setting for the treatment of non-melanoma skin cancer.